Knee injury and osteoarthritis outcome score comparing functional outcome in 30 anterior cruciate ligament reconstruction patients with quadriceps, hamstrings and peroneus longus grafts - Handralmath, Sunil; Dudhanale, Akshay; Dadhaniya, Ravikumar; Wasekar, Manish (International Journal of Research in Orthopaedics, 2024)
Background: Anterior cruciate ligament (ACL) tears are prevalent, affecting 30–78 per 100,000 individuals annually. Graft options include hamstring tendon, bone-patellar-tendon-bone, and quadriceps tendon. Hamstring tendon grafts offer advantages, including less patellofemoral crepitation, anterior knee pain, extension loss, reduced donor site morbidity, and smaller incisions. The peroneus longus tendon graft has gained favor due to fewer knee joint complications. Research shows studies comparing hamstring tendon (HT) and peroneus longus tendon (PLT) grafts revealed no significant differences in pre- and 1-year post-surgery outcomes. Recent randomized controlled trials (RCTs) comparing quadriceps tendon (QT) and HT clinical outcomes found no significant differences in functional outcomes, PROs, laxity testing, or revision rates, although two studies reported higher knee flexor strength in the QT group and greater knee extensor strength in the HT group. Methods: Authors planned for prospective study in tertiary care government hospital, Solapur from 1 July 2023 to 1 July 2024 with Inclusion criteria of 20-50 years, Intact collateral ligaments, Intact Posterior cruciate ligaments, Playing sports as recreational activity. Results: 30 cases operated for ACL reconstruction at our institute with three graft choices namely QT, HT, PL and knee osteoarthritis outcome score given at 3 months, 6 months, and 1 year with KOOS/symptoms, pain, daily living, sports, quality of life all noted separately and compared within the groups and outside the groups. Conclusion: To compare functional scores in post operative ACL reconstruction with QT, HT, PL larger volume of sample, longer follow up and more detailed arthroscopy specific scoring system is required.